Somatic Oximetry Monitoring in a Patient with Fournier Gangrene - Şeyma Yüksel; Esra Kongur; Ahmet Şen; Ahmet Akyol (Türk Yoğun Bakim Derneği Dergisi)
Fournier’s gangrene is a mortal surgical emergency characterized by rapidly spreading soft tissue necrosis between fascial planes in the perineum and genital area. The goal of treatment is early debridement of necrotic tissues to improve tissue oxygenation. In the treatment of this case, somatic oximetry monitoring, which is a non-invasive method, was applied in addition to hemodynamic monitoring to evaluate the effectiveness of fluids, antibiotics and debridements more closely. In the efficacy of the treatment, it was observed that rSO2 values correlated with other laboratory and follow-up parameters.